2000
DOI: 10.1046/j.1462-5822.2000.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania promastigotes require lipophosphoglycan to actively modulate the fusion properties of phagosomes at an early step of phagocytosis

Abstract: SummaryThe lipophosphoglycan (LPG) of Leishmania promastigotes plays key roles in parasite survival in both insect and mammalian hosts. Evidence suggests that LPG decreases phagosome fusion properties at the onset of infection in macrophages. The mechanisms of action of this molecule are, however, poorly understood. In the present study, we used a panoply of Leishmania mutants displaying modi®ed LPG structures to determine more precisely how LPG modulates phagosome±endosome fusion. Using an in vivo fusion assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 63 publications
8
103
1
2
Order By: Relevance
“…Bars, 10 m. Salzer and Prohaska, 2001;Snyers et al, 1998). However, they differ in their subcellular distributions, which include the plasma membrane, phagosomes, lipid droplets, Golgi vesicles, mitochondria, the nucleus and now the ER (Dermine et al, 2000;Garin et al, 2001;Gkantiragas et al, 2001;Green et al, 2004;Morrow et al, 2002;Salzer and Prohaska, 2001;Tatsuta et al, 2005;Umlauf et al, 2004). Proteins with a PHB domain are highly conserved throughout evolution and are found within diverse kingdoms including those of plants, bacteria and animals (Morrow and Parton, 2005;Tavernarakis et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Bars, 10 m. Salzer and Prohaska, 2001;Snyers et al, 1998). However, they differ in their subcellular distributions, which include the plasma membrane, phagosomes, lipid droplets, Golgi vesicles, mitochondria, the nucleus and now the ER (Dermine et al, 2000;Garin et al, 2001;Gkantiragas et al, 2001;Green et al, 2004;Morrow et al, 2002;Salzer and Prohaska, 2001;Tatsuta et al, 2005;Umlauf et al, 2004). Proteins with a PHB domain are highly conserved throughout evolution and are found within diverse kingdoms including those of plants, bacteria and animals (Morrow and Parton, 2005;Tavernarakis et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are reminiscent of the situation with macrophages, for which it has been demonstrated that promastigotes, unlike amastigotes, are located in phagosomes that poorly fuse with late endocytic/lysosomal compartments. This phenomenon could be linked to the stage-specific expression of lipophosphoglycan, the predominant surface glycoconjugate of promastigotes (8,9,19). The promastigote-containing phagosomes with low fusogenic activity were shown to display an impaired recruitment of Rab7 (29).…”
Section: Discussionmentioning
confidence: 99%
“…LPG expression is thought to enhance resistance against toxic serum components such as complement [42][43][44], and in the case of L. donovani and L. major, LPG expression contributes to early promastigote survival in macrophages [45,46]. Upon infection the parasites quickly undergo metamorphosis from promastigotes to amastigotes, which depending on the species, express very little or no LPG [5].…”
Section: Discussionmentioning
confidence: 99%